Rare bird documentation form for Northern Goshawk at Fremont Township in Bremer County, 1982 - Moore, Francis L.et al (1982)
Rare bird documentation form for a Northern Goshawk at Fremont Township in Bremer County, IA on December 18, 1982. Epson - sheet feed